Whey composition as influenced by milk pH, pasteurization, coagulation temperature and whey dilution - Potter, D. R. B.(David Richard Beveridge) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- Universiteit van Stellenbosch, 1962.